Spatially Confined Intervention of Cellular Senescence by a Lysosomal Metabolism Targeting Molecular Prodrug for Broad‐Spectrum Senotherapy. Issue 12 (27th January 2022) - Xia, Yinghao; Li, Jili; Wang, Linlin; Luo, Xiyuan; Xie, Yuqi; Liu, Yanlan
Abstract: Specific intervention of senescent cells (SnCs) is emerging as a powerful means to counteract aging and age‐related diseases. Canonical methods are generally designed to target SnC‐associated signaling pathways, which are however dynamically changing and highly heterogeneous in SnCs, significantly limiting the effectiveness. Here, we present a tailor‐made molecular prodrug targeting lysosome dysfunction, a unique feature shared by virtually all types of SnCs. The prodrug comprises three modules all targeting the altered lysosomal programs in SnCs, namely, a recognizing unit towards the elevated lysosome content, a linker cleavable by the activated lysosomal enzyme, and a lysosomotropic agent targeting the increased lysosomal membrane sensitivity. This spatially confined design enables killing broad‐spectrum SnCs, with high specificity over non‐SnCs. Along with in vivo benefits, this work offers a way to significantly expand the applicability of senotherapy in a wide range of diseases. Abstract : A spatially confined prodrug activation strategy is reported as a new paradigm of senotherapy. The prodrug is designed to target the defective lysosome metabolism, a unique yet ubiquitous event during cellular senescence, instead of dynamically changing and highly heterogeneous senescence‐related signaling pathways employed in conventional methods, thereby fulfilling robust specificity and broad‐spectrum activity towards senescent cells.